Sistem Pakar Diagnosis Penyakit Diabetes Mellitus Dengan Menggunkan Metode Naive Bayes Berbasis Web (Studi Kasus : Puskesmas Kecamatan Sambit Ponorogo) - Aristanto, Rudi; Chandra , Albert Yakobus (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
Diabetes mellitus is a disease characterized by high blood sugar (glucose) levels. DM is known as the silent killer because the sufferer is not aware of it and is identified when complications has already occured.Complications experienced by patients at the Sambit District Health Center were based on the results of interviews. 20% of patients at the Sambit District Health Center suffered from complications. This increasing number is due to delays in diagnosis and unhealthy lifestyles as well as a lack of information so that many patients are diagnosed after complications occured. Early diagnosis will reduce the risk of complications. From this point, an expert system is needed as a diagnostic tool whether the patient suffers from diabetes mellitus or not. Based on this problem, the Naive Bayes algorithm is chosen because it is based on classification by comparing old data and new data, and from this problem the compiler classifies a person who suffers from Diabetes Mellitus with those who are not at the level of symptoms suffered by looking at the events that have passed. From the results of tests that have been carried out from 20 patient data, the percentage of accuracy of the system is 100% (based on facts and symptoms). From this study, it can be concluded that diabetes mellitus is a dangerous disease and still requires early prevention.